Terminally ill head and neck cancer patients and AI: Opportunities and prospects - Gargi S. Sarode; Sachin C. Sarode (Oral Oncology Reports)
Head and Neck Cancer (HNC) presents unique challenges due to its psychological impact, particularly regarding facial disfigurement and social acceptance issues, especially in advanced stages and among terminally ill patients. Despite the critical importance of advance care planning and end-of-life discussions, these aspects are often overlooked, further compounded by the stigma and negative quality of life issues associated with visible morbidity in HNC patients. This commentary explores the potential of Artificial Intelligence (AI) in addressing the multifaceted needs of terminally ill HNC patients. These include pain management and symptom control through predictive modeling, psychosocial support via AI-powered chatbots, treatment decision support by synthesizing patient data, automated radiation planning, end-of-life planning with AI-driven decision support systems, facilitating family communication through structured guidance and emotional support, and legacy building using AI-enabled digital platforms for preserving personal narratives. We propose the AI's potential in reducing suicidal ideation among HNC patients, a significant concern in the HNC patient population. AI can enhance patient safety and promote psychological well-being during the end-of-life journey. This commentary underscores the transformative role of AI in improving the holistic care and quality of life of terminally ill HNC patients, offering practical and compassionate support throughout their challenging journey.